Acquiring new customers by price comparison sites vs. direct marketing: Long-term effects on customer loyalty and cross-buying in a contractual setting - Musiol, Andreas; Steul-Fischer, Martina (2020)

Behavioral Pricing bei Dienstleistungen – Experimentelle Ergebnisse zu ausgewählten Fragestellungen - Steul, Martina (2008)

Clinical trials: Considerations for researchers and hospital administrators - Uecke, Oliver; Reszka, R.; Linke, J.; Steul, Martina; Posselt, Thorsten (Health Care Management Review, 2008)

Consumer Behavior in E-tailing: The Role of Shipping and Restocking Fees - Posselt, Thorsten; Steul, Martina (2008)

Consumers’ service cancellation: Examining the influence of payment timing, refunds and consumption enthusiasm - Steul, Martina; Posselt, Thorsten (European Advances in Consumer Research, 2008)

Customer Experience Management – Eine qualitative Studie zur Umsetzung in der Versicherungsbranche - Klopfer, Lisa-Marie; Steul-Fischer, Martina; Zitzmann, Armin (Zeitschrift für die gesamte Versicherungswissenschaft, 2022)

Customer Referral Programs: How Demographic Similarity, Risk Profile of the Product, and Referral Channels Influence Referral Success - Musiol, Andreas; Steul-Fischer, Martina; Pescher, Christian (NA – Advances in Consumer Research, 2019)

Customer Relationship Management als Integrationsaufgabe - Behnam, F.; Steul, Martina; Beck, M. (bank und markt, 2000)

Default acceptance and ego-depletion: The moderating role of individual versus dyadic decision making - Grösch, Michaela; Steul-Fischer, Martina (2020)

Defaults and advice in self-customization procedures of insurance - Grösch, Michaela; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2017)

Der Einfluss der Produktart und des Weiterempfehlungskanals auf den Erfolg von Weiterempfehlungen bei Versicherungen - Musiol, Andreas; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2019)
For many insurance providers referral programs are a promising customer acquisition tool. Previous research work has been widely studied successful referrals, thereby neglecting unsuccessful referrals. In an empirical study, we examine potential drivers of successful referral likelihood. In particular, we analyze the impact of tie strength (weak ties vs. strong ties) and referral channels (personal vs. written) on the likelihood of successful referrals, and the moderating role of product type (life insurance vs. non-life insurance). Based on customer data from an insurance provider, we show that the likelihood of successful referrals substantially depends on strong social ties (i.e., both the referring and the referred person are living in the same household). Further, a positive interaction effect between tie strength and product type reveals that successful referral likelihood is not merely a result of tie strength: Strong-tie (weak-tie) referrals yield higher (lower) successful referral likelihood for life insurances as compared to non-life insurances. Finally, we show that successful referral likelihood also depends on the choice of the referral channel. Referrals that are mentioned across verbal (written) referral channels yield higher (lower) successful referral likelihood for life insurances as compared to non-life insurances.
CRIS-Team Scopus Importer:2019-07-09

Determining Factors of Customers' Channel Choice in an Omnichannel Environment - A Systematic Literature Review - Wolf, Lukas; Steul-Fischer, Martina (2021)

Die Honorarberatung im Versicherungswesen, in: Versicherungswirtschaft– im Wandel wirtschaftsrechtlicher und rechtsökonomischer Analysen mit Finanzmarkt- und Freiberufsrecht – Festschrift für Prof. Dr. Harald Herrmann - Steul-Fischer, Martina; Bender, Oliver (IF Verlag, 2011)

Die Macht der Weiterempfehlung. Weiterempfehlungsprogramme als vielversprechende Alternative der Neukundenakquise und Kundenbindung - Klopfer, Lisa-Marie; Steul-Fischer, Martina (Vb Versicherungsbetriebe, 2022)

Die Wirkung der Produktpräsentation auf die Abschlussentscheidung und die Entscheidungszufriedenheit bei Versicherungsprodukten - Kirsch, Jürgen; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2016)

Digitalisierte Beratungsunterstützung im Versicherungsvertrieb - Musiol, Andreas; Steul-Fischer, Martina; Gatzert, Nadine (Versicherungsvermittlung, 2018)

Does the framing of investment portfolios influence risk-taking behavior? Some experimental results - Steul, Martina (Journal of Economic Psychology, 2006)

Exploring the influence of submission devices on customer referral creation and receiver reactions in customer referral programs - Wolf, Lukas; Klopfer, Lisa-Marie; Steul-Fischer, Martina; Reinsperger, Maximilian (Journal of Consumer Behaviour, 2024)
Customer referral programs (CRPs) are considered an effective means of customer acquisition through which firms stimulate existing customers to refer services and products to potential new customers. Digitalization and technological developments have led to the common practice of using digital devices like smartphones or laptops to create and submit customer referrals. This is the first study to investigate the influence of submission devices in CRPs from both the sender's and receiver's perspective. Based on four experiments, we demonstrate that smartphone-generated referrals are shorter and less positive than those composed on laptops/PCs. These differences in text length and valence negatively influence receiver responses, leading to lower purchase intentions due to the perceived usefulness of the referral mediating this relationship. Our findings underscore the important role of submission devices for online referral behavior and contribute to the growing body of research on device-mediated consumer behavior, offering crucial insights to optimize the promotion and design of CRPs.<br

Factors of Customers’ Channel Choice in an Omnichannel Environment: A Systematic Literature Review - Wolf, Lukas; Steul-Fischer, Martina (Proceedings of the European Marketing Academy, 51st (106350), 2022)
The proliferation of mobile devices and the continuous development of online technologies has led to an increasing variety of channels, leaving today’s customers with a choice of channel alongside the choice of product, service, or retailer. Any attempt to optimize customer experience and engage in successful omnichannel management will require a complete understanding of the processes around customers´ channel choice. This study conducted a systematic literature review to the end of identifying the factors involved in channel choice which appear in the scientific literature. The analysis of 111 relevant papers retrieved from bibliographic databases highlighted five principal categories of factors: the characteristics of a particular channel, customer needs, situation and context, customer characteristics, and characteristics of products or services. Alongside its presentation of an integrated conceptual framework, the review details a comprehensive agenda for future research.

Factors of customers’ channel choice in an omnichannel environment: a systematic literature review - Wolf, Lukas; Steul-Fischer, Martina (Management Review Quarterly, 2023)
The proliferation of mobile devices and the continuous development of online technologies has led to an increasing variety of channels, leaving customers with a choice of channel alongside the choice of product, service, or retailer. Any attempt to optimize customer experience and engage in successful omnichannel management will require a complete, multifaceted understanding of the processes around channel choice of customers. To date, the many existing studies around multi- and omnichannel research have failed to yield an integrated, comprehensive synthesis of factors involved in customers´ channel choice. Our study conducted a systematic literature review to the end of identifying the factors involved in channel choice which appear in the scientific literature on this topic over the last two decades. We retrieved 128 papers from three bibliographic databases (EBSCO Host, Scopus, and Web of Science) and carried out descriptive analysis on them. Qualitative thematic analysis inductively extracted 66 different factors of channel choice, each assignable to five broader categories, from the studies included in the review. The findings indicate that perceived channel characteristics, customer needs and situational or contextual factors influence customers´ channel choice directly, and customer characteristics and characteristics of products or services influence it indirectly. Alongside its presentation of an integrated conceptual framework comprising these relationships, our study details a comprehensive research agenda with regards to theories, contexts, and methods and, in particular, with regards to factors influencing customers´ channel choice. Our findings advance the academic understanding of channel choice behavior and provide researchers and practitioners in this area with information on important implications for omnichannel management.<br
Keywords: Channel choice; Omnichannel management; Multichannel management; Consumer behavior; Customer behavior; Systematic literature review

Framing Effects and Information Processing of Individual Investors - Steul, Martina (European Advances in Consumer Research, 2006)

Honorarberatung – Einstellung und Relevanz auf dem Versicherungsmarkt - Bender, Oliver; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2012)
In the area of insurance intermediaries, fee-based advisory is the widely discussed alternative type of remuneration to the standard commission system. The aim of this study is to comprehensively analyze the attitude of independent insurance brokers to the direct commission system. In total, 23 interviews with experts were conducted to gather insights into the significance and the behaviour of insurance brokers. Thus, differences (level of attitude) between the interviewed experts as well as factors influencing their attitudes can be identified. © Springer-Verlag 2012.
WiSo-Import:2015-03-26:4163

How Default Effects and Decision Timing Affect Annuity Uptake and Health Consciousness - Unger, Franziska; Steul-Fischer, Martina; Gatzert, Nadine (The Geneva Papers on Risk and Insurance - Issues and Practice, 2022)

How digital devices shape online recommendations - Klopfer, Lisa-Marie; Wolf, Lukas; Steul-Fischer, Martina (Proceedings of the European Marketing Academy, 52nd, 113943, 2023)

How do consumers handle service cancellations? - Posselt, Thorsten; Steul, Martina (2007)

How Does Device Choice Differ Along the Customer Journey and for Different Product Characteristics? – Insights From Experimental and Clickstream Data - Wolf, Lukas; Steul-Fischer, Martina (Proceedings of the European Marketing Academy, 52nd, 112703, 2023)

Influence of Future Time Perspectives on Involvement: an Approach With Two Studies - Scholz, Stefanie; Illich-Weber, Yvonne; Ivens, Björn; Steul-Fischer, Martina (NA – Advances in Consumer Research, 2012)

Integration der Verlustangst von Kunden in den Verkaufsprozess - Steul-Fischer, Martina; Kreitmair, Michaela; Schmidt-Gallas, Dirk (Versicherungswirtschaft, 2014)

Less is more: How the number of insurance options influences customers’ default acceptance - Grösch, Michaela; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2018)

Live Healthy and Get Rewarded – The Impact of Reward Type and Timing in Pay-As-You-Live Pricing - Unger, Franziska; Steul-Fischer, Martina (Proceedings of the European Marketing Academy, 51st (107046), 2022)
Pay-as-you-live (PAYL) pricing as a new and promising service pricing mechanism has emerged in health insurance in order to increase competitive advantage among insurance companies and healthy lifestyles among consumers. PAYL tariffs reward consumers health-promoting behavior with a discount on the insurance premium or a monetary or nonmonetary reward accordingly. We conducted an experimental study to investigate the impact of reward type (monetary vs. nonmonetary) and reward timing (monthly vs. yearly) on consumers' purchase intention of PAYL tariffs and health behavior intention. The results show that reward evaluation mediates the influence of reward type on consumers’ purchase intention of a PAYL tariff. We observe a higher reward evaluation for monetary compared to nonmonetary rewards. Monthly rewards lead to significantly higher health behavior intentions than yearly rewards. The higher the purchase intention of a PAYL tariff, the higher the health behavior intention.

Optimierung des Customer Experience Managements durch die Nutzung von Speech Analytics in der Versicherungsbranche - Klopfer, Lisa-Marie; Meier, Giulia; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2024)

Please don’t tell me, I don’t want to know it in detail – Framing and Perception of Increased Prices for Car Insurances - Zagel, Timo; Steul-Fischer, Martina (2013)

Presenting Health Information: The Effects of Attribute Framing, Numercial Framing and Graphical Presentation on Health Risk Perception - Eberle, Silvia; Steul-Fischer, Martina (2020)

Presenting Health Information: The Influence of Attribute and Numerical Framing on Health Risk Perception - Heideker, Silvia; Steul-Fischer, Martina (NA - Advances in Consumer Research, 2017)

Price framing and consumers´purchase intention on pay-how-you-drive tariffs - Musiol, Andreas; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2019)
Pay-how-you-drive (PHYD) is an innovative car insurance tariff offered by insurance companies, whereby prices are based on an individual’s driving style and mileage. In an experimental study, we analyze the effect of price framing on purchase intention for PHYD tariffs. Results demonstrate that consumers’ purchase intention for a PHYD tariff is higher for integrated price framing compared to segregated price framing. Also, we show that the amount of discount (surcharge) on the price moderates the effect of price framing on purchase intention for a PHYD tariff. Finally, we show that the sureness effect (i.e., sureness about having no unexpectedly high billing rates due to variation in driving style and mileage) mediates the effect of price framing and on purchase intention for PHYD tariff.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Car insurance; Consumer experience; Framing; Pay-how-you-drive

Quantitative Marketingforschung in Deutschland – Festschrift für Klaus Peter Kaas zum 65. Geburtstag - Steul, Martina (Duncker & Humblot Verlag, 2005)

Reputationsmanagement von Versicherungsunternehmen in Social Networks - Kottler, Gabriele; Steul-Fischer, Martina; Burkhardt, Jörg (Zeitschrift für die gesamte Versicherungswissenschaft, 2015)

Rewards for a healthy lifestyle – the impact of reward type and timing in pay-as-you-live pricing - Unger, Franziska; Steul-Fischer, Martina (Marketing - Forschung und Praxis - Journal of Research and Management, 2023)

Risikoeinstellung, Risikoverhalten und Marketing für Finanzdienstleistungen. Arbeitspapier Nr. 24 - Schade, Christian; Steul, Martina (1998)

Risikoeinstellung, Risikoverhalten und Marketing für Finanzdienstleistungen - Schade, Christian; Steul, Martina (1999)

Risikoverhalten privater Kapitalanleger – Implikationen für das Finanzdienstleistungsmarketing - Steul, Martina (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2003)

Social Intranets in Multinational Companies: A Qualitative Study - Weichbrodt, Johanna; Steul-Fischer, Martina; Burkhardt, Jörg (2014)

Starting Points´ Effects on Risk-Taking Behavior - Schade, Christian; Steul, Martina; Schröder, Andreas (2002)

Sunday gleich Funday? Die Analyse und Prognose von Zeiteffekten im Online-Kundenverhalten im Versicherungsbereich mittels Machine Learning. - Wolf, Lukas; Galehr-Fritsch, Elisabeth; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2024)

The Effect of Affective States on the Willingness to Pay for Insurance and their Role over Time - Steul-Fischer, Martina; Wiersich, Matthias (2014)

The Effect of Emotions on the Willingness to Pay for Insurances - Wiersich, Matthias; Steul-Fischer, Martina (2012)

The Effect of Familiarity and Dread on Health Risk Perception. - Heideker, Silvia; Steul-Fischer, Martina (AP - Asia Pacific Advances in Consumer Research, 2015)

The Effect of Flat Shipping Fee and Free Shipping Threshold on Consumer Evaluations - Koukova, Nevena T.; Srivastava, Joydeep; Steul-Fischer, Martina (European Advances in Consumer Research, 2011)

The effect of message framing and the presentation of health vs. social consequences on health risk perception - Unger, Franziska; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2020)
With health prevention campaigns health insurance providers can increase the perception of health risks among customers in order to promote healthy behaviour. The presentation format of health information has a significant influence on the health-related behaviour of customers. We investigate in our experimental study the impact of positive vs. negative presentation (message framing) as well as the presentation of health vs. social consequences in health prevention campaigns on health risk perception. The results reveal that loss- (vs. gain-) framed messages and the presentation of health (vs. social) consequences increase health risk perception more strongly. This effect is mediated by a stronger perceived severity of health (vs. social) consequences. Women perceive health (vs. social) consequences more likely and closer in time than men. Our findings show the importance of increasing health risk perception in order to promote healthy behaviour intentions.
CRIS-Team Scopus Importer:2020-07-31

The Effect of Option Framing in Self-Other Decision Making - Grösch, Michaela; Steul-Fischer, Martina (Marketing - Forschung und Praxis - Journal of Research and Management, 2019)

The Effect of Option Framing on Consumer Choice for Service Options - Kreitmair, Michaela; Steul-Fischer, Martina (AP - Asia Pacific Advances in Consumer Research, 2015)

The effect of shipping fee structure on consumers’ online evaluations and choice - Koukova, Nevena T.; Srivastava, Joydeep; Steul-Fischer, Martina (Journal of the Academy of Marketing Science, 2012)
This research examines how consumers respond to different shipping fee structures. Focusing on two of the most common shipping fee structures, flat rate shipping and threshold-based free shipping, we first demonstrate that offer evaluations are less (more) favorable with threshold-based free shipping when order value is below (above) the free shipping threshold compared to flat rate shipping. However, when an alternative more important referent is present, the effect of shipping fee structure is attenuated. Second, we show that although perceptions of shipping fees as a profit generator are higher (lower) under threshold-based free shipping relative to flat rate shipping for order values below (above) the free shipping threshold, providing a justification for the shipping fee by explicitly linking it to delivery costs encourages consumers to view the shipping fee as a cost of doing business rather than as a profit generator, thus raising offer evaluations. © 2011 Academy of Marketing Science.
WiSo-Import:2015-03-26:4162
Keywords: Flat rate shipping; Free shipping; Online shopping; Progressive rate shipping; Shipping fee; Threshold-based free shipping

The Effect of Shipping Fee Structures on Consumer Evaluations of Online Offers - Koukova, Nevena T.; Srivastava, Joydeep; Steul-Fischer, Martina (Advances in Consumer Research, 2010)
WiSo-Import:2015-03-26:4739

The Effects of Message Framing and Ad Credibility on Health Risk Perception - Heideker, Silvia; Steul-Fischer, Martina (Marketing-Forschung und Praxis - Journal of Research and Management, 2017)

The influence of the used device on recommendation behavior online - Klopfer, Lisa-Marie; Steul-Fischer, Martina; Wolf, Lukas (2022)

The psychological effects on tariff choices for car insurance - Musiol, Andreas; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2017)

The Use of Message Framing, Temporal Framing and Consequence Type to Increase Consumers’ Health Risk Perception - Unger, Franziska; Steul-Fischer, Martina (Proceedings of the European Marketing Academy, 50th (93308), 2021)

To win or not to win – Efficiency, Passive Selection and Awards in Tournaments for Insurance Sales Agents - Wedel, Michaela; Steul-Fischer, Martina (2015)

Turnierentlohnung als Anreizsystem im Versicherungsvertrieb - Steul-Fischer, Martina; Wedel, Michaela (Controlling, 2015)

Turnierentlohnung im Versicherungsbetrieb - Steul-Fischer, Martina; Wedel, Michaela (2010)
WiSo-Import:2015-08-12:1537
Keywords: Innovation; Forschungsbericht 2010

Turnierentlohnung im Versicherungsvertrieb - Steul-Fischer, Martina; Wedel, Michaela (Zeitschrift für die gesamte Versicherungswissenschaft, 2012)
For insurance companies, tournaments are one of the most important incentives to motivate and control insurance sales agents. We analyse the efficiency of tournaments for insurance sales agents and show that the level of prize and its exclusiveness, as well as the presentation of rank during the tournament, increase efficiency. © Springer-Verlag 2012.
WiSo-Import:2015-03-26:4164

Versicherungsentscheidungen und der Einfluss von Emotionen - Steul-Fischer, Martina; Wiersich, Matthias (2011)
WiSo-Import:2015-08-12:3111

Versicherungsunternehmen in Social Networks - Ein Überblick über aktuelle Forschungsfelder und eine experimentelle Studie zur Kundenansprache - Burkhardt, Jörg; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2013)
Due to changing customer demands Social Networks become increasingly important in insurance business life. This study provides a comprehensive analysis of both the traditional and new approaches of Social Network research. Based on this analysis we present categorized implications that show evidence for future research. We take up the research question from the category "communication and marketing" in order to experimentally investigate different kinds of customer communication in Social Networks. Our results show that the kind of customer communication has an impact on the willingness to comply. Thus, the kind of customer communication could be a critical criterion for the success of an insurance company in Social Networks. © 2013 Springer-Verlag Berlin Heidelberg. Literatur:.
WiSo-Import:2015-03-26:4736

Wahrgenommene Preisfairness bei Preiserhöhungen in der Schadenversicherung - Zagel, Timo; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2014)

Was komplexe Beratungsgespräche erfolgreich macht - Steul-Fischer, Martina; Möller, Antje (bank und markt, 2018)

Weiterempfehlungsprogramme: Die Wirkung des Akquisitionskanals und der Prämienaufteilung auf den Erfolg von Weiterempfehlungen - Klopfer, Lisa-Marie; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2020)
Referral programs are established as a marketing tool in the insurance industry, as they offer an effective and cost-efficient alternative to traditional methods of customer acquisition and retention, such as direct marketing. Previous research on referrals and referral reward programs primarily focused on the referral likelihood of existing customers. However, successful referrals also require the willingness of the recipient to accept the referral. This empirical study therefore focuses on the referral recipient and the determinants of referral acceptance. The results reveal that customers who have been acquired through a company’s referral reward program (acquisition channel) generate a higher likelihood of successful referral compared to customers acquired through other marketing activities (e.g. direct marketing). Furthermore, sharing the referral reward between sender and receiver of the referral leads to a higher likelihood of successful referral than rewarding the referrer only (reward allocation). This effect is mediated by the perceived fairness of the reward allocation.
CRIS-Team Scopus Importer:2020-07-10

Werbeanzeigen von Versicherungsunternehmen zur Aufklärung über Gesundheitsrisiken - Heideker, Silvia; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2016)